2014
DOI: 10.1002/ijop.12039
|View full text |Cite
|
Sign up to set email alerts
|

Motivational cues: The role of perceived senders' self‐control ability in raters' deception judgements

Abstract: Previous studies have found that senders' personal traits may be used by others to make judgements about the senders' truthfulness. Two studies were conducted to examine whether perceived self-control ability has an effect on deception judgement. Perceived self-control was hypothesized to act as a motivational cue that participants would use to assess the sender's motivation to lie, which in turn would influence their deception judgement. Results revealed that when participants assessed the sender as having hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Both phenomena can be explained to some extent by using too much context‐general information. Second, most studies about context‐general information have concentrated on people's traits, such as their abilities (Wu et al, ) or appearance (Masip et al, ). The present study demonstrated that a person's words can also be regarded as context‐general information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both phenomena can be explained to some extent by using too much context‐general information. Second, most studies about context‐general information have concentrated on people's traits, such as their abilities (Wu et al, ) or appearance (Masip et al, ). The present study demonstrated that a person's words can also be regarded as context‐general information.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have proposed a very similar hypothesis, which we call the deception cue hypothesis here, that there are two different cues in deception judgments: informational cues and motivational cues (Wu, Cai, Zou, & Jin, ; Wu, Zou, Cai, Wang, & Jin, ). Informational cues, just like the individuating information, refer to verbal or nonverbal information that can be used to judge whether a specific statement is true or not.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Research on this topic can be divided into two approaches. The first focuses on characteristics of the sender, such as verbal content or nonverbal behaviours (Reinhard & Sporer, ), physical appearance (Berry & McArthur, ; Masip, Garrido, & Herrero, ), social skills (Riggio, Tucker, & Throckmorton, ), and abilities (Wu, Cai, Zou, & Jin, ; Wu, Zou, Cai, Wang, & Jin, ). The second approach focuses on characteristics of the receiver, such as motivation (Wu, Cai, & Jin, ), involvement (Reinhard & Sporer, ), and personal traits (Ein‐Dor & Perry, ).…”
Section: Introductionmentioning
confidence: 99%